Odpowiedź:
1]
I sposób:
x²+t²-2ax-2by+c=0
x²+y²+12x-2y+10=0
-2a=12 a=-6 -2b=-2 b=1 S=( -6,1)
r=√( a²+b²-c)=√(36+1-10)=√27=3√3
II metoda:
x²+y²+Ax+By+C=0
x²+y²+12x-2y+10=0 A= 12 B = -2 C= 10 S=(a,b)
a= -A/2=-12/2=-6 b=-B/2= 2/2=1 S=(-6,1)
r= √[ (A²/4)+(B²/4)-C]=√[144/4 + 4/4 -10]=√(36+1-10)=3√3
2)
(x-a)²+(y-b)²=r²
(0-a)²+(0-b)²=r² a²+b²=r²
(-6-a)²+(0-b)²=r² 36+12a+a²+b²=r²
(-6-a)²+(8-b)²=r² 36+12a+a²+64-16b+b²=r²
a²+b²=r²
a²+b²+12a+36=r²
a²+b²+12a-16b+100=r²
a²+b²=a²+b²+12a+36 12a=-36 a=-3
a²+b²=a²+b²+12a-16b+100 12*(-3) -16b+100=0 16b= 64 b= 4
r²=(-3)²+4²= 25
(x+3)²+(y-4)²=25
Szczegółowe wyjaśnienie: